2009
DOI: 10.1111/j.1440-1746.2009.05917.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions to azathioprine cannot be predicted by thiopurine S‐methyltransferase genotype in Japanese patients with inflammatory bowel disease

Abstract: The frequency of TPMT gene mutations is low among Japanese IBD patients. The incidence of adverse reactions to AZA was high, even in patients carrying wild-type TPMT. It is concluded that determination of TPMT genotype may not be useful in Japanese IBD patients to predict adverse reactions to AZA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
123
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 28 publications
6
123
1
Order By: Relevance
“…Many patients with high level tolerated this metabolite level. It is previously reported that Asians have higher likelihood of thiopurine toxicity 21, 34. We had lowest toxicity as compared with that reported in the literature and did not observe any hepatotoxicity.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Many patients with high level tolerated this metabolite level. It is previously reported that Asians have higher likelihood of thiopurine toxicity 21, 34. We had lowest toxicity as compared with that reported in the literature and did not observe any hepatotoxicity.…”
Section: Discussionsupporting
confidence: 52%
“…There is a poor correlation between weight‐based dosing of thiopurines and 6‐TGN and 6‐MMP levels 26. Previous studies have suggested that Asian patients do not tolerate full doses of thiopurines and have more toxicity 10, 18, 19, 20, 21. However, as mentioned above, these studies were based on estimation of TPMT genotype and activity rather than drug metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in 15-30% of patients, these drugs have to be discontinued due to adverse effects including bone marrow suppression, hepatotoxicity, pancreatitis, fever, rash and gastrointestinal intolerance (4)(5)(6)(7)(8)(9). Furthermore, an AZA dosage of 2-3 mg/kg is recommended for the treatment of IBD patients in Western countries (10), but lower doses of AZA (0.6-1.2 mg/kg/day) are used in Japanese patients due to their relatively heightened sensitivity (11).…”
Section: Introductionmentioning
confidence: 99%
“…It catalyses the thiopurines S-methylation (4,17,22). TPMT enzyme activity is inherited as an autosomal codominant sign and is under the control of genetic polymorphisms that have been extensively studied in the past (21).…”
mentioning
confidence: 99%